Prevalence of interstitial and other lung diseases on Aruba - Deenstra, Duco; Wolvetang, Niek; Kock, Selene; Wills, Stuart; Cobben, Nicolle; Wijnen, Petal; Drent, Marjolein (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Health care management has to be based on the local prevalence of diseases and the local diagnostic and therapeutic needs. So far, no systematic registration system for various lung diseases exists on Aruba. Questions that need to be answered are: what specific lung disorders occur on Aruba, and what are the specific needs there? The aim of this study was to assess the prevalence of lung disorders and the diversity of the patient population. Methods: Retrospectively, all records (n=2352) of patients of the Department of Respiratory Diseases of the Dr. Horatio E. Oduber Hospital, Aruba, who were seen at the clinic at least once in the period between January 2010 and October 2014 were reviewed. Results: Asthma (22%) and sleeping disorders (20%) were the most prevalent diagnoses. The mean body mass index (BMI) of the overall lung patient population was 31.6 kg/m2. Obstructive sleep apnea syndrome (OSAS) was the most frequently diagnosed sleeping disorder (78.4%). A diagnosis of interstitial lung diseases (ILD) was established in 4.4% of the cases. Among the ILDs, non-specific interstitial pneumonia (NSIP: 28%), sarcoidosis (18%) and idiopathic pulmonary fibrosis (IPF: 16%) were the most frequent. Conclusion: Obesity and OSAS appeared to be major problems on Aruba. Increased awareness, education, and diagnostic facilities are required to prevent and diagnose obesity and OSAS in an early stage. NSIP, sarcoidosis and IPF are the most frequently diagnosed ILDs on Aruba, and optimization of ILD management is warranted, considering new treatment options available for ILD, especially for IPF.